2017
DOI: 10.1002/cssc.201701274
|View full text |Cite
|
Sign up to set email alerts
|

Dry Reforming of Methane in a Gliding Arc Plasmatron: Towards a Better Understanding of the Plasma Chemistry

Abstract: Dry reforming of methane (DRM) in a gliding arc plasmatron is studied for different CH fractions in the mixture. The CO and CH conversions reach their highest values of approximately 18 and 10 %, respectively, at 25 % CH in the gas mixture, corresponding to an overall energy cost of 10 kJ L (or 2.5 eV per molecule) and an energy efficiency of 66 %. CO and H are the major products, with the formation of smaller fractions of C H (x=2, 4, or 6) compounds and H O. A chemical kinetics model is used to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
93
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 87 publications
(137 reference statements)
2
93
2
Order By: Relevance
“…[15][16][17] Nonthermal plasma (NTP) approach has been used as an alternative to thermocatalytic methods. Various NTP systems such as corona discharges, [18] atmospheric plasma jet, [19] gliding arcs, [20][21][22] glow discharge, [23] and dielectric barrier discharges (DBDs) [24][25][26] have been tested for DRM and CO 2 mitigation. Among all, DBD attracted more attention due to the uniform distribution of microdischarges, presence of high energetic electrons, capability of initiating the reaction under ambient conditions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Nonthermal plasma (NTP) approach has been used as an alternative to thermocatalytic methods. Various NTP systems such as corona discharges, [18] atmospheric plasma jet, [19] gliding arcs, [20][21][22] glow discharge, [23] and dielectric barrier discharges (DBDs) [24][25][26] have been tested for DRM and CO 2 mitigation. Among all, DBD attracted more attention due to the uniform distribution of microdischarges, presence of high energetic electrons, capability of initiating the reaction under ambient conditions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ni catalysts are probably among the most commonly used due to their effectiveness and low costs, they are versatile and have been used in numerous reactions . One of the reactions is dry reforming of methane (DRM), in which two greenhouse gases (CH 4 and CO 2 ) are converted to valuable syngas (H 2 and CO) . Ni catalysts for DRM, also true for other reactions, are prepared by various methods, e. g., impregnation, co‐precipitation, sol‐gel, polymerization, hydrothermal,, and more recently plasma treatment,, and atomic layered deposition ,.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] One of the reactions is dry reforming of methane (DRM), in which two greenhouse gases (CH 4 and CO 2 ) are converted to valuable syngas (H 2 and CO). [13][14][15][16][17] Ni catalysts for DRM, also true for other reactions, are prepared by various methods, e. g., impregnation, [18][19][20][21] coprecipitation, [22][23][24][25] sol-gel, [26][27][28] polymerization, [29] hydrothermal, [30,31] and more recently plasma treatment, [32,33] and atomic layered deposition. [34,35] A reduction process usually follows to obtain active metal phase.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma DRM technology is considered the best way to convert CO 2 and CH 4 to synthesis gas . Plasma, the fourth state of matter, is a partially ionised gas mixture consisting of ions, atoms, electrons, molecules, free radicals, neutral by‐products, and photons . Generally, the plasma process is divided into two main methods: The first is cold plasma (nonthermal plasma) discharge including dielectric barrier discharge, corona discharge, atmospheric pressure glow discharge, gliding arc discharge, microwave discharge, and spark discharge .…”
Section: Introductionmentioning
confidence: 99%
“…In the nitrogen‐plasma process, CO 2 and CH 4 conversion and selectivities of H 2 and CO are affected by many factors such as feed gas flow rate, CO 2 :CH 4 ratio, reactor design, residence time, and discharge power . Several authors have proved that the effect of feed gas flow rates of CO 2 , CH 4 , and N 2 is an effective factor in the performance of the plasma process. First, Cleiren et al reported that the feed flow rate affects the conversion, selectivity, yield, and syngas (H 2 /CO) ratio.…”
Section: Introductionmentioning
confidence: 99%